Jornalismo literário como narrativa da realidade : teoria e expressão em Vozes de Tchernóbil - Pereira, Andreza Silva (2024)
This work aims to analyze contemporary literary journalism from the perspective of narrative studies. Literary journalism can be conceived as a phenomenon of hybridization between journalism and literature, a textual form referenced in reality and invested with the aesthetic function of language. The hybridity of this object of study is taken as a narrative expression, like that of other objects of culture invested with meaning, and framed in the theoretical space expanded contemporaneously by the socalled “narrative turn” (BROCKMEIER and HARRÉ, 2003). Literary journalism is still thought as narrative in an expanded literary field (KRAUSS, 2012), borrowing fictional creative resources — notably from realistic prose — in a crossing of experimentation with languages, discourses, genres. It is to this impure and borderline textual in-between place of literary journalism that thesis looks, aiming to recognize in it the narrative syntax of reality. As a hypothesis to the problem of characterizing literary journalism as narrative, it is stated that the general characters of meaning construction and poetics associate this journalism to the narrative phenomenon. The methodologies to guide this study are bibliographic review, considering its essential theoretical nature, and Narrative Analysis (MOTTA, 2013). An attempt is made to review the basic literature on the subject, building an interdisciplinary path between the fields of literature and social communication, in order to seek grounds for the proposed hypothesis. Through Narrative Analysis, as an approach of the concepts raised in a movement compelled by theory towards the corpus, a non-fiction book about a historical trauma (SELIGMANNSILVA, 2008) — Vozes de Tchernóbil, by Svetlana Aleksiévitch — is added to the discussion.